1991
DOI: 10.1149/1.2086014
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Aromatic Compounds in Organic Chloroaluminate Melts: I . Phenazine

Abstract: The electroreduction of phenazine in basic mixtures of A1C13 and 1-ethyl-3-methyl-lH-imidazolium chloride (EMIC) (44.4 mole percent A1C13) has been investigated by electrochemical and spectroscopic techniques. Initial results suggested that the reduction of phenazine proceeded through a two-electron process coupled with two protonations to form dihydrophenazine. However, further investigation, using authentic dihydrophenazine, indicated that this reduction product was not the result of proton exchange reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…34−37 Phenazine and its derivatives have been widely used as broad-spectrum antibiotics. 38 It has been found that phenazine shows reversible redox properties in water−DMF mixtures, 39,40 but its insolubility in water hinders the application in ARFBs. Through the grafting of triethylene glycol (TEG) linkers or sulfonate groups, the solubility of phenazine derivatives can be increased to different extents.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…34−37 Phenazine and its derivatives have been widely used as broad-spectrum antibiotics. 38 It has been found that phenazine shows reversible redox properties in water−DMF mixtures, 39,40 but its insolubility in water hinders the application in ARFBs. Through the grafting of triethylene glycol (TEG) linkers or sulfonate groups, the solubility of phenazine derivatives can be increased to different extents.…”
mentioning
confidence: 99%
“…The degradation mechanism of organic molecules in nonaqueous system has been widely studied for many years, while the capacity fade mechanism of organic redox-active species in aqueous systems has attracted rising attention over the last 5 years. To date, the redox reversibility of water-soluble organic molecules has been successfully extended to varying degrees. Phenazine and its derivatives have been widely used as broad-spectrum antibiotics . It has been found that phenazine shows reversible redox properties in water–DMF mixtures, , but its insolubility in water hinders the application in ARFBs. Through the grafting of triethylene glycol (TEG) linkers or sulfonate groups, the solubility of phenazine derivatives can be increased to different extents. , Meanwhile, the effects of different functional groups of phenazine derivatives on the aqueous solubility, electrochemical redox properties, and cycling stability are waiting to be further explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…197 Elsewhere the formation of polyfluorene was achieved by Janiszewska and Osteryoung. 200,201 The use of a neat ionic liquid 1-methyl-3-ethylimidazolium hydrogen dichloride [C 2 -mIm][HCl 2 ] was also investigated with regard to the reduction of phenazine. The reactions studied dealt with the reduction of aromatic ketones.…”
Section: Electrosynthesismentioning
confidence: 99%
“…198 Actual transformation of an organic moiety was achieved electrochemically in 1-methyl-3-butylimidazolium chloroaluminate systems. 200 Most of the work in electrosynthesis has been carried out in air-and moisture-sensitive ionic liquids, those containing chloroaluminates and [HCl 2 ] -; little investigation into the electrosynthetic possibilities presented by air and moisture stable ionic liquids has been attempted. 199 Reductions of perylene and phenazine have also been achieved electrochemically in basic mixtures of aluminum trichloride and 1-methyl-3-ethylimidazolium chloride.…”
Section: Electrosynthesismentioning
confidence: 99%